A study about the solutions of Schrödinger equation with an asymptotically linear potential - Filho, Elso Drigo [UNESP] (My University, 1996)
We determine the solutions of the Schrödinger equation for an asymptotically linear potential. Analytical solutions are obtained by superalgebra in quantum mechanics and we establish when these solutions are possible. Numerical solutions for the spectra are obtained by the shifted 1/N expansion method.